Implementasi Metode Technology Accaptance Model (TAM) untuk Mengukur Aplikasi Sistem Informasi Universitas Putra Indonesia YPTK - Muhammad Afdhal; Dhio Saputra (LPPM Universitas Potensi Utama, 2026)
The development of information technology in education has encouraged of implementation of integrated information systems to improve academic, administrative, and service processes; however, their effectiveness is strongly influenced by the level of user acceptance. This study aims to measure the acceptance of the Academic Information System at Universitas Putra Indonesia YPTK using the Technology Acceptance Model (TAM). The novelty of this study lies in the development of an extended TAM model by integrating Information Quality (INQ), System Quality (SYQ), and Service Quality (SVQ) as quality factors mediated by User Satisfaction (USF) in influencing Net Benefit (NBF). A quantitative descriptive approach was employed involving 108 respondents consisting of students, lecturers, and administrative staff. Data were collected using a Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM). The results indicate that System Quality (SYQ) is the strongest predictor of User Satisfaction (USF), which subsequently has a dominant effect on Net Benefit (NBF), thereby validating the model as an effective evaluation framework to support system quality improvement and digital transformation in higher education.